Creation of a Collaborative Disaster Preparedness Video for Daycare Providers: Use of the Delphi Model for the Creation of a Comprehensive Disaster Preparedness Video for Daycare Providers. (22nd February 2018) - Mar, Pamela; Spears, Robert; Reeb, Jeffrey; Thompson, Sarah B.; Myers, Paul; Burke, Rita V.
Abstract: Objective: Eight million American children under the age of 5 attend daycare and more than another 50 million American children are in school or daycare settings. Emergency planning requirements for daycare licensing vary by state. Expert opinions were used to create a disaster preparedness video designed for daycare providers to cover a broad spectrum of scenarios. Methods: Various stakeholders (17) devised the outline for an educational pre-disaster video for child daycare providers using the Delphi technique. Fleiss κ values were obtained for consensus data. A 20-minute video was created, addressing the physical, psychological, and legal needs of children during and after a disaster. Viewers completed an anonymous survey to evaluate topic comprehension. Results: A consensus was attempted on all topics, ranging from elements for inclusion to presentation format. The Fleiss κ value of 0.07 was obtained. Fifty-seven of the total 168 video viewers completed the 10-question survey, with comprehension scores ranging from 72% to 100%. Conclusion: Evaluation of caregivers that viewed our video supports understanding of video contents. Ultimately, the technique used to create and disseminate the resources may serve as a template for others providing pre-disaster planning education. ( Disaster Med Public Health Preparedness . 2019;13:123–127)